Mapeamento de escolas públicas bilíngues no Brasil: potencialidades e limites de uma nova tecnologia social - Resende, Brenda Gonçalves de (2023)
We are currently experiencing a growth in the offering of bilingual education within private educational institutions in Brazil. However, even though it is not widely spread as a public policy, bilingual public schools of choice have also emerged in the Brazilian context in recent years. Due to being a scarcely addressed topic, this dissertation arises to identify, locate, and map these schools. With an exploratory and descriptive nature, the research aimed to identify, locate, and map these institutions. Data was collected through the Access to Information Act, and the analysis involved a qualitative-quantitative approach. The results revealed the existence of 93 bilingual public schools in Brazil, spread across the states of Amazonas, Tocantins, Maranhão, Paraíba, Distrito Federal, Minas Gerais, Rio de Janeiro, and Santa Catarina. Additionally, the qualitative analysis indicated that these schools represent concrete manifestations of Social Technology in the country. This study contributes to understanding this growing phenomenon and lays the groundwork for future investigations and the development of more inclusive and empowering educational policies.